Exploring the Themes and Stylistic Features in the Works of Mary Ann Evans (George Eliot) (International Journal of Food and Nutritional Sciences, 2019)
The research study explores the literary legacy of Mary Ann Evans, renowned by the pen name George Eliot, a prominent figure in Victorian literature. Eliot's influential works have made a lasting impact on the realist tradition. The article is dedicated to probing the themes and stylistic nuances embedded in her notable novels, including Middlemarch, Adam Bede, and Silas Marner. Through a thorough analysis, the study aims to unveil the intricacies of Eliot's literary craftsmanship, shedding light on her substantial role in shaping nineteenth-century realism.